Application of Baby Gymnastics with Lullaby Music as A Gross Motor Stimulation in Babies Aged 3-12 Months: Penerapan Senam Bayi dengan Musik Lullaby sebagai Stimulasi Motorik Kasar pada Bayi Usia 3-12 Bulan - Dita, Inggrit Supra; Sofiana, Juni; Namah, Lutfia Uli (Prosiding University Research Colloquium, 2023)
Introduction: The coverage of Indonesian children with gross motor development disorders is 12.4%, while developmental delays in toddlers in Central Java Province are 24.5%. Factors that influence developmental disorders include internal factors and external factors. The consequences that can occur in children who experience gross motor development disorders are not being able to carry out basic functional movements such as lifting their heads, crawling, standing and walking, while the long-term consequences that can be experienced are children becoming less interested in learning, doubtful, insecure and anxious. was in the surroundings. One thing that can be done to stimulate gross motor skills is by applying baby exercises and listening to lullaby music. Purpose: To provide midwifery care for baby gymnastics with lullaby music as gross motor stimulation for infants aged 3-12 months. Methods: This research is a type of case study. The participants in this study were 4 respondents who met the inclusion and exclusion criteria. Data obtained from observation and interviews. Results: After doing baby exercises with lullaby music for 2 weeks, there were 4 participants (100%) who experienced an increase in gross motor development to become more optimal. This is based on an assessment using KPSP at the beginning and end of implementation. Conclusion: The application of baby gymnastics with lullaby music is able to improve the gross motor development of infants according to the age stage.